Bacterial Pathogens Hijack the Innate Immune Response by Activation of the Reverse Transsulfuration Pathway - Alain P. Gobert; Yvonne L. Latour; Mohammad Asim; Jordan L. Finley; Thomas G. Verriere; Daniel P. Barry; Ginger L. Milne; Paula B. Luis; Claus Schneider; Emilio S. Rivera; Kristie Lindsey-Rose; Kevin L. Schey; et al. (mBio, 2019)
ABSTRACT The reverse transsulfuration pathway is the major route for the metabolism of sulfur-containing amino acids. The role of this metabolic pathway in macrophage response and function is unknown. We show that the enzyme cystathionine γ-lyase (CTH) is induced in macrophages infected with pathogenic bacteria through signaling involving phosphatidylinositol 3-kinase (PI3K)/MTOR and the transcription factor SP1. This results in the synthesis of cystathionine, which facilitates the survival of pathogens within myeloid cells. Our data demonstrate that the expression of CTH leads to defective macrophage activation by (i) dysregulation of polyamine metabolism by depletion of S-adenosylmethionine, resulting in immunosuppressive putrescine accumulation and inhibition of spermidine and spermine synthesis, and (ii) increased histone H3K9, H3K27, and H3K36 di/trimethylation, which is associated with gene expression silencing. Thus, CTH is a pivotal enzyme of the innate immune response that disrupts host defense. The induction of the reverse transsulfuration pathway by bacterial pathogens can be considered an unrecognized mechanism for immune escape. IMPORTANCE Macrophages are professional immune cells that ingest and kill microbes. In this study, we show that different pathogenic bacteria induce the expression of cystathionine γ-lyase (CTH) in macrophages. This enzyme is involved in a metabolic pathway called the reverse transsulfuration pathway, which leads to the production of numerous metabolites, including cystathionine. Phagocytized bacteria use cystathionine to better survive in macrophages. In addition, the induction of CTH results in dysregulation of the metabolism of polyamines, which in turn dampens the proinflammatory response of macrophages. In conclusion, pathogenic bacteria can evade the host immune response by inducing CTH in macrophages.